EIB Working Paper 2022/07 - Corporate training and skill gaps - European Investment Bank (2022)
"The availability of talent and skills has been a significant investment obstacle for firms across the EU over the years, with several sources highlighting the persistence and prevalence of skill shortages. In this paper, we use the European Investment Bank's Investment Survey (EIBIS) for the empirical analysis, which allows tracking corporate training investment on a yearly basis. To understand the reasons for firms' decision to invest in their workforce, we examine transition patterns and employ dynamic panel data estimation. We also analyse the impact of COVID-19 on firms' investment in workforce training and transitions in and out of training. Despite a slow upward trend in training investment observed in recent years supported by labour market recovery, differences across firms and countries have persisted. The pandemic risks aggravating these differences, through its uneven impact on labour markets and differences in corporate innovation, firm structure and resilience. While firm training can be an important element for firms and their workforce to adjust to the post-pandemic environment, asymmetries in training investment could make it harder for those already lagging. The paper concludes with a discussion of policy implications."